Faktor-Faktor Yang Mempengaruhi Menopause Dini: Tinjauan Literatur - Ni Putu Ayu Mira Kusuma Dewi; Ni Luh Kadek Alit Arsani; Ni Putu Dewi Sri Wahyuni (LPPM ITEKES Mahardika, 2025)
Menopause is a natural phase marking the end of a woman’s reproductive period, with the average age in Indonesia being 49.98 years. However, the prevalence of early menopause has increased from 14% in 2019 to 20.2% in 2021, impacting quality of life and raising the risk of degenerative diseases. This study aims to examine the factors influencing early menopause through a literature review. Findings show that this condition is shaped by a complex interaction of various factors. Biological factors such as age at menarche, age at childbirth, and contraceptive use are associated with the timing of menopause. Lifestyle factors including physical activity, diet, smoking habits, stress, and weight-loss drug use also play a role. Health history such as chronic illness, hormonal disorders, and non-ideal body mass index can accelerate menopause. Socio-demographic factors, including education and occupation, affect women’s health behavior and knowledge. Therefore, early menopause is the result of biological, lifestyle, health, and social interactions. Education, health promotion, and interventions are needed to prepare women and reduce its negative impacts. Keywords: Menopause Factors, Reproductive Health, Early Menopause.